Manfaatan Media Audiovisual Sebagai Strategi Pembelajaran Diferensiasi di MTs Nurul Islam Indonesia - Hairun Tsaniah Azhari; Anggi Agustiani Samosir; Cindy Cintiya Nst; Ulfia Husna; Surya Dermawan Damanik (JALIYE: Jurnal Abdimas, Loyalitas, dan Edukasi, 2025)
This study aims to describe the utilization of audiovisual media as a differentiated learning strategy at MTs Nurul Islam Indonesia. The background of this research is based on the diversity of students’ characteristics in terms of learning styles, abilities, and levels of understanding, which requires adaptive and inclusive learning strategies. This research employed a descriptive qualitative approach, with data collected through classroom observations, interviews with teachers and students, and documentation of learning activities. The results indicate that audiovisual media were systematically utilized in the learning process as an introduction to the material, a means of concept explanation, and a tool for reinforcing students’ understanding. The integration of audiovisual media with group discussion activities was able to accommodate differences in students’ learning abilities, increase learning motivation and classroom participation, and enhance conceptual understanding. Furthermore, the role of teachers was found to be crucial in the successful implementation of differentiated learning, particularly in managing media use, facilitating discussions, and providing constructive feedback. This study concludes that the use of audiovisual media as a differentiated learning strategy can serve as an effective alternative to create meaningful, participatory, and equitable learning experiences in madrasah education.